Investigating the frequency of alleles of crtRB1 and LcyE genes that are favoable for -carotene accumulation in some maize lines cultivated in VietNam - Luong, Tran Thi; Thanh, Nguyen Duc (Academia Journal of Biology, 2018)
Provitamin A carotenoid content, including b-carotene in corn kernels is very low and varies widely in maize lines /varieties. Results of the study on the role of the crtRB1 and LcyE gene alleles in the accumulation of b-carotene in maize showed that some alleles could regulate the increase in b-carotene content. These alleles are called favorable alleles as they are favorable for b-carotene accumulation. However, the frequency of these alleles in traditional maize varieties is very low. And so they are known as rare alleles. The identification of favorable alleles and high b-carotene maize lines for maize improvement in the direction of increased provitamin A carotenoid content, especially b-carotene, is very important. In this study, we investigated the frequency of alleles of the crtRB1 and LcyE genes that are favorable for β-carotene accumulation in 20 maize lines cultivated in Vietnam. The results showed that the favorable allele frequency of crtRB1 in the studied maize lines was 25% and that of LcyE was 5%. Four lines (H240, H95, H20 and Ngô nâu vàng Lắk, Đắk Lắk) carry favorable alleles at 3’ end of crtRB1 gene and have high b-carotene content (from 6,100 to 17,247 mg/g). These maize lines are an important source for researches in the improvement of b-carotene content in maize.